1995
DOI: 10.1111/j.1365-2133.1995.tb02711.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone propionate 0.05% cream in the treatment of atopic eczema: a multicentre study comparing once-daily treatment and once-daily vehicle cream application versus twice-daily treatment

Abstract: The aim of this study was to compare the efficacy and safety of once-daily with twice-daily application of a 0.05% cream formulation of fluticasone propionate in the treatment of atopic eczema in adults and children. Two hundred and seventy patients with moderate to severe atopic eczema were enrolled in the study, and randomized to receive either once-daily or twice-daily fluticasone propionate 0.05% cream for 4 weeks. Patients randomized to the once-daily group also received the vehicle cream to ensure that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 0 publications
0
31
1
5
Order By: Relevance
“…It is the opinion of the expert work group, that less frequent application (eg, for moderately severe AD of the flexural folds) or more frequent application (eg, for AD of the hands where required frequent hand washing may prohibit optimal absorption) may occasionally be used without a significant resultant alteration in the manufacturers reported efficacy and safety. 19,21,38,43,44 In one large systematic review, it was found that using twice-daily applications was no more effective than once-daily application. 21 The approach of using short bursts of potent steroids compared to longer term use of weaker corticosteroids demonstrated no differences in children with mild to moderate AD.…”
Section: Discussionmentioning
confidence: 97%
“…It is the opinion of the expert work group, that less frequent application (eg, for moderately severe AD of the flexural folds) or more frequent application (eg, for AD of the hands where required frequent hand washing may prohibit optimal absorption) may occasionally be used without a significant resultant alteration in the manufacturers reported efficacy and safety. 19,21,38,43,44 In one large systematic review, it was found that using twice-daily applications was no more effective than once-daily application. 21 The approach of using short bursts of potent steroids compared to longer term use of weaker corticosteroids demonstrated no differences in children with mild to moderate AD.…”
Section: Discussionmentioning
confidence: 97%
“…Bleehen et al, showed that the once daily treatment with the fluticasone propionate 0.05% cream in atopic eczema was as effective as the twice daily treatment [14].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of FP cream and ointment have been established in many clinical studies, including some in infants and young children and where treatment has been applied repeatedly for up to 9 months. 1,[3][4][5][6]8,9,12,13 FP lotion is a new product and has been developed as an alternative formulation, one that has good spreadability and beneficial emollient properties. The safety data presented in this study demonstrated that under exaggerated conditions of use, in the most vulnerable patient groups, FP 0.05% lotion was well-tolerated and did not affect HPA axis function or produce drug-related atrophogenic changes.…”
Section: Discussionmentioning
confidence: 99%